The Impact of Innovativeness on Supply Chain Performance: Mediating Role of Supply Chain Integration - Haider Mukhtar; Snober Fazal (iRASD Journal of Management)
The purpose of this research is to test the innovativeness impact on supply chain (SC) performance by using the mediating effect of SC integration, as well as by taking into account the moderating effect of information system capability in the manufacturing sector of small and medium enterprises (SMEs) in South Punjab Pakistan. The research is based on a survey questionnaire. Non-probability convenience sampling was used, and 251 responses were collected from the SMEs' Owners/CEOs/managers. The findings show that innovativeness has a favorable effect on SC integration, which in turn has a positive effect on SC performance. The findings imply a moderating effect on the link between SC integration and performance. The findings imply that organizations should strive for innovation and SC integration since they contribute to SC performance. The distinctiveness of this study derives from its attention to SC performance is used, which is explored through the mediating effect of SC integration, as well as by taking into account the moderating effect of information system capability in the manufacturing sector of SMEs in South Punjab, Pakistan.